Konsep Etika Keutamaan dalam Tasawuf Abdul Qadir Al-Jailani dan Pengaruhnya terhadap Terbentuknya Akhlak Manusia - Sofiatus Sholeha; Ainur Rofiq Sofa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the concept of ethical virtue in the teachings of Sufism of Abdul Qadir al-Jailani and its relevance in the formation of modern human character. According to al-Jailani, purification of the soul is a key element in achieving moral perfection. This process consists of several spiritual stages, namely repentance, which means returning to Allah with regret and determination to improve oneself; zuhud, freeing oneself from worldly attachments; tawakal, which is surrendering oneself completely to the will of Allah; patience, being steadfast in facing all life's tests; honesty, behaving according to the truth; gratitude, always being grateful for all the blessings given; and ridha, accepting all His decisions sincerely. These stages aim to improve individual morals and guide them towards a better life spiritually and ethically. This study uses a library research method with a qualitative approach, in which content analysis techniques are applied to comprehensively understand al-Jailani's teachings. The results of the study indicate that the concept of ethical virtue taught by al-Jailani is very relevant in the development of human character, both in the past and the present. His teachings can be integrated into the modern ethical and moral education system as an effort to form individuals with noble morals. The appreciation of these values allows humans to live more meaningfully, have good morals, and contribute to creating a more dignified society. In facing modern moral challenges, such as materialism and individualism, al-Jailani's teachings can be a relevant and sustainable ethical guide.